PENERAPAN MODEL PEMBELAJARA QUANTUM TEACHING SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN BERBICARA PADA SISWA KELAS V SEKOLAH DASAR - sinaga, marlina; Maryono, Maryono; Noviyanti, Silvia (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
Language skills have an important role for a person in carrying out daily activities or at work. Just like speaking, it is a normal human life activity and is important for being able to interact with other humans in life. This research is classroom action research (PTK) which consists of two cycles with 4 stages, namely planning, implementing actions, observing and reflecting. The data collected in this research is data regarding the learning process using the Quantum Teaching learning model and students' speaking skills obtained through observation data collection techniques, unstructured interviews and performance. Data was analyzed qualitatively and quantitatively to measure changes that occurred in students' speaking skills. The results of the research show that by applying the Quantum Teaching learning model it is possible to improve students' speaking skills in learning starting from cycle 1, the first meeting obtained results with an average score of 2.5 and at the second meeting it reached 2.51. In cycle II, the first meeting obtained results with a value of 2.56 and in the second meeting, success and improvement reached an average value of 2.85.